A HYBRID MULTI-CRITERIA DECISION-MAKING MODEL FOR ENERGY EFFICIENCY PRACTICES IN INDONESIA'S TEXTILE INDUSTRY - Hendra, Mulia
Energy plays important role for the socioeconomic development of nations, espe- cially in manufacturing sectors like the textile industry. Energy consumption di- rectly affects production costs and market competitiveness. Therefore, implement- ing energy efficiency practices is crucial. However, implementation of energy ef- ficiency measures are complex management problems due to various influencing